Interprofessional collaboration between health professional learners when breaking bad news: a scoping review protocol. Issue 8 (20th August 2021) - Lackie, Kelly; Miller, Stephen; Ayn, Caitlyn; Brown, Marion; Helwig, Melissa; Houk, Shauna; Lane, Jennifer; Mireault, Amy; Neeb, David; Picketts, Leanne; Stilwell, Peter; Beatty, Lorri
ABSTRACT: Objective: The objective of this scoping review is to examine pedagogies used to teach interprofessional health learners how to break bad news collaboratively. Introduction: Breaking bad news is a skill health care professionals must be equipped to deliver well, yet literature shows that this skill receives little attention in program curricula. Consequently, health care professionals feel inadequately prepared to deliver bad news, leading to greater burnout, distress, and fatigue. Inclusion criteria: Studies that describe pedagogies used to teach breaking bad news will be considered for inclusion. Studies must include two or more undergraduate and/or postgraduate learners working towards a professional health or social care qualification or degree at a university or college. Studies including lay, complementary and alternative, or non-health or social care professional learners will be excluded. Methods: The JBI three-step process will be followed for developing the search. Databases to be searched include MEDLINE, CINAHL, Embase, Education Resource Centre, and Social Work Abstracts. Title and abstract screening through to data extraction will be completed by two independent reviewers and any disagreements will be resolved through discussion, or with a third reviewer. Results will be presented in tabular or diagrammatic form, together with a narrative summary.